ISO 23247 Digital Twin Model for JIT Supply Chain Visibility: Model Digital Twin ISO 23247 untuk Visibilitas Rantai Pasok JIT - Riyanto, Rudy; Karningsih , Putu Dana; Al Kindhi , Berlian (Indonesian Journal of Innovation Studies, 2026)
General Background: Automotive supply chains operating under Just-in-Time (JIT) principles require high levels of supply chain visibility to maintain synchronized material flow and stable production rhythms. Specific Background: In practice, daily monitoring using the Material Information Flow Chart (MIFC) remains constrained by paper-based tools or non-integrated digital systems, resulting in information lead times of one to two weeks and limited support for real-time problem solving. Knowledge Gap: Although Digital Twin technology and ISO 23247 architecture provide a standardized digital representation framework, limited studies address structured integration of conventional MIFC with ISO 23247 for cross-supply chain material flow representation in JIT environments. Aims: This study proposes the design of an ISO 23247–based MIFC Digital Twin model (MIFCDT) to represent material flow through structured digital entities aligned with Observable Manufacturing Elements and standard information attributes. Results: The model maps seven MIFC symbols into OME Equipment and OME Process entities and formulates digital representations using identifier, characteristics, location, capacity, and dynamic status attributes capturing timestamp and quantity data. A conceptual automotive supply chain scenario demonstrates one-to-one correspondence between physical and digital entities, enabling structured monitoring of cycle time deviation and lead time delay. Novelty: The study introduces a structured digital representation model that bridges conventional MIFC practice with ISO 23247 architecture at the material flow level. Implications: The proposed model provides a conceptual foundation for real-time supply chain visibility and supports daily management in JIT-based automotive systems while opening pathways for further empirical implementation. Highlights • Structured mapping of seven MIFC symbols into ISO 23247 Observable Manufacturing Elements.• Formulation of static and dynamic digital attributes capturing timestamp, quantity, and location data.• One-to-one correspondence between physical production points and digital entities demonstrated in a conceptual automotive scenario. Keywords Digital Twin; ISO 23247; Supply Chain Visibility; Just-In-Time; Material Information Flow Chart